An Agency Theory Perspective on the Purchase of Marketing Services - Tate, Wendy L.; Ellram, Lisa M.; Bals, Lydia; Hartmann, Evi; van der Valk, Wendy (Industrial Marketing Management, 2010)
<span style="color: rgb(46, 46, 46); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: 16px; word-spacing: -1.24453px;">The purchase of business services has become an important part of organizations' acquisition of external resources, and is therefore receiving growing scholarly attention. The supply management function is increasingly supporting more complex service purchases, including a wide range of marketing services. The trend to involve supply management in the purchase of these complex business services is partially being driven by increasing awareness of the value of applying standard purchasing techniques to the purchase of these non-standard items. The purchase of such services has historically been managed by content experts, with limited involvement of supply management. However, the involvement of supply management in these purchases is driving the content experts to adopt a more facilitating relationship in which both areas interact with the supplier. This research uses Agency Theory as a lens to look at the Agency Triad among supply management, marketing, and suppliers. Elaborating on prior seminal work, the basic tenets of Agency Theory and its assumptions regarding human behavior are combined with the results of a focus group and case studies to develop propositions on the design of contractual arrangements between two Principals (marketing and supply management) and a single Agent who provides marketing services.
Keywords: Marketing services; Supply management; Service purchasing; Agency Theory